Desiring machines and nomad spaces: neoliberalism, performativity and becoming in senior secondary drama classrooms. Issue 2 (4th March 2017) - Lambert, Kirsten; Wright, Peter; Currie, Jan; Pascoe, Robin
ABSTRACT: This paper explores Deleuze and Guattari's schizoanalysis in relation to student and teacher becomings and the way these are actualised within the neoliberal and heterosexually striated spaces of the secondary school assemblage. Deleuze and Guattari considered a narrow approach to education problematic and called for creativity as a site of 'resistance'. Drama is one subject rich with potentiality for students to strengthen their creativity and 'speak back' against the neoliberal project. What our research revealed is how the drama classroom is an open, dynamic space where students can embody different identities at a critical time in their adolescent development. What is delimiting about this potentiality is the proclivity of teachers and students, as desiring machines, to conform to the dominant neoliberal culture of competitive performativity. The paper proposes that schizoanalysis offers new insights for mapping complex desire-flows and embodied identities through and against the dominant performative and heterosexist culture.